Clinical value of ultrasound for the evaluation of local recurrence of primary bone tumors - Wang, Yu; Yu, Ping; Liu, Feifei; Wang, Yuqin; Zhu, Jiaan (Frontiers in Oncology, 2022)
Background: Early detection of local recurrence would improve the survival rate of patients with recurrent bone tumors. There is still no consensus on how to follow up after surgery of primary malignant bone tumors. Therefore, the purpose of this study is to evaluate the diagnostic value of ultrasound (US) for local recurrence after limb salvage by comparing with other imaging modalities. Methods: We retrospectively reviewed the medical records of patients who were regularly examined by US in our hospital after primary bone tumor surgery from January 2016 to December 2019, some of which underwent X-ray, computed tomography (CT) or 99mTc-MDP bone scan. Recurrence was determined by pathologic confirmation. The cases were considered a true negative for no recurrence if no clinical or pathologic evidence for recurrence was found at least 6 months after the US examination. The Chi-square test or Fisher exact test was used to compare categorical data. P values < 0.0083 were considered statistically significant. Results: 288 cases were finally enrolled in our research, including 66 cases with pathologic results. The sensitivity of ultrasound was 95.0%, higher than that of X-ray (29.6%) (P=0.000). The accuracy of ultrasound was 96.9%, higher than that of X-ray (85.6%) (P=0.000). Conclusion: As a nonradiative and cost-effective examination, US may be used as a routine imaging method for postoperative surveillance of primary bone tumors, especially those with metal implants, if more multicenter prospective studies can be done in the future.